Morphological characteristics and phylogenetic analyses revealed Lopharia guangdongensis sp. nov. (Polyporaceae, Basidiomycota) from Southern China - Guo, Wei; Jiang, Qianquan; Zhou, Hongmin (Phytotaxa, 2026)
One new wood-inhabiting fungus, Lopharia guangdongensis, found in Guangdong Province, Southern China, is described here based on its morphology and phylogeny. Lopharia guangdongensis is characterized by its coriaceous basidiomata, smooth hymenial surface, a monomitic hyphal system with simple-septa generative hyphae, and oblong ellipsoid basidiospores measuring 8.8–11 × 5–6.5 µm. Phylogenetic analyses of the new species are carried out based on the nuclear ribosomal internal transcribed spacer (ITS) and the nuclear large subunit (nLSU) of ribosomal DNA. The phylogenetic tree revealed that the studied materials represent a distinct lineage, closely related to L. ayresii within the genus Lopharia, based on ITS+nLSU sequences. A full description, illustrations, and phylogenetic analyses results of the new species are provided.